A combination of in silico and wet-lab strategies towards the identification of biomarkers of endometrial cancer progression and aggressiveness - Argibay, Maria Cecilia (2019)
Endometrial cancer (EC) is the 2nd most frequent gynecological neoplasm, expecting a > 50% increase in the next 20 years. Current diagnosis is based on abnormal uterine bleeding, transvaginal ultrasound or uterine biopsy or curettage with or without hysteroscopy. Final diagnosis and tumor classification is done during hysterectomy. Although highly relevant, there are no established EC molecular biomarkers.